2008
DOI: 10.1590/s0100-204x2008000200007
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética de pacu do Rio Paranapanema e do estoque de um programa de repovoamento

Abstract: Resumo -O objetivo deste trabalho foi estudar a diversidade genética das amostras de pacu do médio Rio Paranapanema e do estoque de reprodutores utilizado no programa de repovoamento da Estação de Aqüicultura e Hidrologia da usina hidrelétrica Duke Energy, por meio do marcador RAPD. Genetic diversity of pacu from the Paranapanema River and from the broodstock of a stock enhancement programAbstract -The objective of this work was to study the genetic diversity of pacu samples from the middle Paranapanema River… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
(16 reference statements)
2
10
0
4
Order By: Relevance
“…The authors, however, recognize that the fact of releasing hatchery reared immature fish inside the reservoir could have influenced the results. Povh et al (2008) using RAPD markers detected moderate population differentiation between 29 pacu from the broodstock of the Estação de Aquicultura e Hidrobiologia of the Duke Energy power plant (formed by 250 fish from rio Paraná) and 30 pacu captured on the fish ladders of the Canoas I and II reservoirs located in the mid rio Paranapanema. On the other hand, in the upper rio Paraná, in a region that is free of dams, Revaldares et al (1997) analysed 19 isozymes in Prochilodus lineatus from the rios Paraná, Ivinheima and Baia and although the authors detected high polymorphims and heterozygosity the Nei's values for genetic similarity were also high indicating that they form a panmitic population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors, however, recognize that the fact of releasing hatchery reared immature fish inside the reservoir could have influenced the results. Povh et al (2008) using RAPD markers detected moderate population differentiation between 29 pacu from the broodstock of the Estação de Aquicultura e Hidrobiologia of the Duke Energy power plant (formed by 250 fish from rio Paraná) and 30 pacu captured on the fish ladders of the Canoas I and II reservoirs located in the mid rio Paranapanema. On the other hand, in the upper rio Paraná, in a region that is free of dams, Revaldares et al (1997) analysed 19 isozymes in Prochilodus lineatus from the rios Paraná, Ivinheima and Baia and although the authors detected high polymorphims and heterozygosity the Nei's values for genetic similarity were also high indicating that they form a panmitic population.…”
Section: Discussionmentioning
confidence: 99%
“…Most population studies on Neotropical fish species seem to point out to some level of population structuring (Hatanaka & Galetti Jr., 2003;Barroso et al, 2005;Povh et al, 2008). Sanches & Galetti Jr. (2007) used RAPDs to assess the genetic variability of 80 individuals of the migratory characin Brycon hilarii at four sites of the rio Miranda subbasin (Paraná-Paraguay basin) and found significant population differences.…”
Section: Conservation Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Lopera-Barrero et al (2008b) in Brycon orbignyanus broodstocks where an offspring with six excluded fragments was reported, or rather, loss of genetic variability when compared with broodstock, but with high intrapopulation genetic variability. Povh et al (2008) also reported four excluded fragments in Piaractus mesopotamicus broodstocks, or rather, a lower genetic variability when compared with natural population. However, the intra-population genetic characterization was high.…”
Section: Variability and Genetic Structurementioning
confidence: 92%
“…Dominant marker in current assay proved efficient in the study of genetic variability. Other studies with the same marker for S. brasiliensis (ALMEIDA et al, 2013;GOMES et al, 2011GOMES et al, , 2013LOPES et al, 2007) and in other fish species (JACOMETO et al, 2010;, 2010LOPES et al, 2009;PAULA et al, 2006;POVH et al, 2008b) also gave positive results. In fact, dominant markers still have great possibilities of information for the initial review of genetic processes in natural populations or in fish stocks.…”
Section: Groupingmentioning
confidence: 81%